Experimental additions of allochthonous dissolved organic matter reveal multiple trophic pathways to stimulate planktonic food webs. (16th March 2023) - Balzer, Matthew J.; Hitchcock, James N.; Hadwen, Wade L.; Kobayashi, Tsuyoshi; Westhorpe, Douglas P.; Boys, Craig; Mitrovic, Simon M.
Abstract: There is still considerable debate as to whether the allochthonous (terrestrial) dissolved organic matter (DOM) mobilised during large flow events plays an important role in supporting secondary production in riverine food webs. Understanding how food webs respond to large pulses of terrestrial DOM (tDOM) is important for conceptualising the relative importance of energy sources supporting food webs. A mesocosm experiment (1, 000 L) using three concentrations of leachate (1, 4, 8 mg C/L and a control) made from floodplain DOM was run for 34 days in a dam filled with water from Gunbower Creek in Northern Victoria, Australia. Nutrients, phytoplankton, zooplankton and stable isotope (δ 13 C signatures) data were collected to examine how floodplain nutrients affected growth and community structure within the lower food web typical of an Australian lowland river. All leachate additions led to very high concentrations of zooplankton and mixotrophic algae compared to the control. Mixotrophs dominated the algal biovolume of all leachate additions until Day (D)20 and appeared to drive changes in δ 13 C signatures of particulate organic matter (POM) which were significantly related to changes in zooplankton δ 13 C signatures. tDOM additions did not significantly suppress obligate autotroph growth which also appeared important as a food source, as reflected in the δ 13 C signatures of zooplankton and POM after D10. These results show the ability of phytoplankton and zooplankton communities in lowland rivers to respond quickly to changes in resource availability and quality. Mixotrophs appeared to provide an important trophic link between allochthonous carbon and primary consumers, and increased complimentarily to autotrophic production. This resulted in large net increases to phytoplankton biovolume and potentially played a significant role in driving changes in zooplankton growth. We suggest that allochthonous DOM may be highly bioavailable and support production through several different trophic pathways, offering a large boost to production via both autotrophy and heterotrophy. Furthermore, we contend that mixotrophy may be an important pathway for allochthonous organic matter to enter riverine food webs and support secondary production.